Determination of biodiesel amount in various biodiesel-diesel blends / Siti Norhafiza Mohd Khazaai … [et al.] - Mohd Khazaai, Siti Norhafiza; Maniam, Gaanty Pragas; Ab. Rahim, Mohd Hasbi; Mohd Alwi, Muhammad Hasnol Fazirin (Universiti Teknologi MARA Cawangan Pahang, 2020)
Biodiesel is an alternative non-toxic fuel with low emission profiles, biodegradable, and environmentally friendly. This study focused in the optimization process of base-catalyzed transesterification of palm oil that produced 97.44 % methyl ester with 60 ºC reaction temperature, 9:1 methanol/oil mass ratio, and 1.2 wt% of catalyst within 1 h. A series of diesel-biodiesel blends of B7, B20, B30, B40, and B100 were prepared by mixing the biodiesel with pure diesel. B100 showed the highest value for all tested parameters (acid value: 0.2596 mg KOH/g; peroxide value: 11.7992 meq/kg; moisture content: 0.45%, flash point: 175 ºC, kinematic viscosity: 5.57 mm2/g and density: 0.8686 g/cm3). The correlation coefficient of the relationship between acid value, peroxide value, moisture content, density, and viscosity were 0.9256, 0.8351, 0.8378, 0.8345, and 0.8452, respectively. Nevertheless, all tested parameters were positively accepted according to ASTM - D6751 standard method. Thus, this may benefit the related industries as well as monetary gain in countering any false claim on the % blend